The digital divide in Papua New Guinea: Implications for journalism education - Maria Sagrista (Asia Pacific Network, 2016)
Access to new technology and the development of the necessary skills to master them are crucial aspects when developing countries aim to play a more important role in the current information age and knowledge-based society. New technology and the internet have the potential to enhance access to information for people and to help countries such as Papua New Guinea become active producers of knowledge, shifting away from the traditional role of passive consumption. However, new technology also has the potential to increase already existing inequalities. In this regard, exploring the concrete shortcuts brought by the digital divide in PNG and trying to address them for journalism education is an imperative, so that journalists in the country can bridge this gap, raise their own voices and best contribute to the development of Papua New Guinean society.